Genetic variation and possible origins of weedy rice found in California - De Leon, Teresa B. (Ecol Evol, 2019)
Control of weeds in cultivated crops is a pivotal component in successful crop production allowing higher yield and higher quality. In rice‐growing regions worldwide, weedy rice (Oryza sativa f. spontanea Rosh.) is a weed related to cultivated rice which infests rice fields. With populations across the globe evolving a suite of phenotypic traits characteristic of weeds and of cultivated rice, varying hypotheses exist on the origin of weedy rice. Here, we investigated the genetic diversity and possible origin of weedy rice in California using 98 simple sequence repeat (SSR) markers and an Rc gene‐specific marker. By employing phylogenetic clustering analysis, we show that four to five genetically distinct biotypes of weedy rice exist in California. Analysis of population structure and genetic distance among individuals reveals diverse evolutionary origins of California weedy rice biotypes, with ancestry derived from indica, aus, and japonica cultivated rice as well as possible contributions from weedy rice from the southern United States and wild rice. Because this diverse parentage primarily consists of weedy, wild, and cultivated rice not found in California, most existing weedy rice biotypes likely originated outside California.